860 Targeting immunosuppressive macrophages overcomes PARP-inhibitor resistance in BRCA1-associated triple-negative breast cancer. (10th December 2020) - Mehta, Anita; Cheney, Emily; Hartl, Christina; Pantelidou, Constantia; Oliwa, Madison; Castrillon, Jessica; Lin, Jia-Ren; Hurst, Katie; Taveira, Mateus de Oliveira; Johnson, Nathan; Oldham, William; Kalocsay, Marian; et al.
Abstract : Background: Despite objective responses to PARP inhibition and improvements in progression-free survival compared to standard chemotherapy in patients with BRCA-associated triple-negative breast cancer (TNBC), benefits are transitory. Methods: Using high dimensional single-cell profiling of human TNBC, here we demonstrate that macrophages are the predominant infiltrating immune cell type in BRCA-associated TNBC. Through multi-omics profiling we show that PARP inhibitors enhance both anti- and pro-tumor features of macrophages through glucose and lipid metabolic reprogramming driven by the sterol regulatory element-binding protein 1 (SREBP-1) pathway. Results: Combined PARP inhibitor therapy with CSF-1R blocking antibodies significantly enhanced innate and adaptive anti-tumor immunity and extends survival in BRCA-deficient tumors in vivo and is mediated by CD8+ T-cells. Conclusions: Collectively, our results uncover macrophage-mediated immune suppression as a liability of PARP inhibitor treatment and demonstrate combined PARP inhibition and macrophage targeting therapy induces a durable reprogramming of the tumor microenvironment, thus constituting a promising therapeutic strategy for TNBC.